2017
DOI: 10.5688/ajpe81226
|View full text |Cite
|
Sign up to set email alerts
|

A Consensus Approach to Investigate Undergraduate Pharmacy Students’ Experience of Interprofessional Education

Abstract: Objective. To assess the development of knowledge, attitudes, and behaviors for collaborative practice among first-year pharmacy students following completion of interprofessional education. Methods. A mixed-methods strategy was employed to detect student self-reported change in knowledge, attitudes, and behaviors. Validated survey tools were used to assess student perception and attitudes. The Nominal Group Technique (NGT) was used to capture student reflections and provide peer discussion on the individual I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…19 Learning with, from and about each other promotes the effective function of a health care team. 20…”
Section: Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Learning with, from and about each other promotes the effective function of a health care team. 20…”
Section: Definitionmentioning
confidence: 99%
“…These themes are not entirely discipline-specific but were particularly noted within the two professions in the IPE literature. 1,[4][5][6]12,14,16,17,20,21,[24][25][26][27]29,33,[39][40][41][42][43] Developing a national network, such as the European Interprofessional…”
Section: Barriers and Facilitators To Interprofessional Education For Dentistry And Pharmacy Studentsmentioning
confidence: 99%
“…IPE is defined by the World Health Organization as "occurring when two or more professions learn about, from and with each other to enable effective collaboration and improve health outcomes" [8]. Pharmacy schools across the nation are beginning to integrate various interprofessional active learning experiences to challenge their students to practice collaboration and apply the concepts learned in their traditional didactic classes [9]. Specifically in North Carolina, all pharmacy schools' didactic coursework includes integrated pharmaceutical and clinical sciences, as well as immersion in direct patient care to prepare students for a future as a clinical practitioner.…”
Section: Current Interprofessional Trainingmentioning
confidence: 99%
“…Students' readiness for IPE and individual, environmental, educational, and sociocultural factors affecting it should be determined so that educators can consider the students' needs while preparing curricula and raise their awareness. There are numerous studies on health science students' readiness for IPE [22][23][24][25][26][27][28][29][30] . Zorek et al (2014) conducted a descriptive study to develop interprofessional readiness measurement tools 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Mafinejad Ahmady, Arabshahi and Bigdeli (2013) and Milutinovic, Lovric and Simin (2018) reported that students' readiness for IPE differed by age, gender, and grade level 2,30 . Although previous studies have determined how readiness for IPE differs across health science student populations, those included only a limited group of students in the samples [22][23][24][25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%